2019
DOI: 10.1111/jrh.12363
|View full text |Cite
|
Sign up to set email alerts
|

Rural‐Urban Disparities in Total Physical Activity, Body Composition, and Related Health Indicators: An Atlantic PATH Study

Abstract: Purpose: To describe and compare the sociodemographic and lifestyle characteristics of urban and rural residents in Atlantic Canada. Methods: Cross-sectional analyses of baseline data from the Atlantic Partnership for Tomorrow's Health cohort was conducted. Specifically, 17,054 adults (35-69 years) who provided sociodemographic characteristics, measures of obesity, and a record of chronic disease and health behaviors were included in the analyses. Multiple linear regression and logistic regression models were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
10
1
Order By: Relevance
“…Residents of urban areas reduced their activities significantly more than residents of rural areas. Older (pre-Covid-19) investigations tend to favor urban areas when it comes to higher PA [ 140 ], but recent studies parallel to this review also show higher PA levels in rural areas [ 141 , 142 ]. Nigg et al [ 93 ] showed that children and adolescents residing in densely populated areas showed less favorable PA changes than children and adolescents living in sparsely populated areas.…”
Section: Discussionmentioning
confidence: 99%
“…Residents of urban areas reduced their activities significantly more than residents of rural areas. Older (pre-Covid-19) investigations tend to favor urban areas when it comes to higher PA [ 140 ], but recent studies parallel to this review also show higher PA levels in rural areas [ 141 , 142 ]. Nigg et al [ 93 ] showed that children and adolescents residing in densely populated areas showed less favorable PA changes than children and adolescents living in sparsely populated areas.…”
Section: Discussionmentioning
confidence: 99%
“…We included both raw deprivation measure values (social/material factor score) and quintiles relative to values from other health regions in the province (positively shifted social/material factor score). The urban form of each residential location was assessed using the Canadian-active living environment index (Can-ALE index),21 a measure of urbanicity, as there is evidence that PA behaviors vary significantly between urban and rural populations 22. The Can-ALE index is derived from an evaluation of the density of intersections and residential dwellings on a scale from 1 (very low) to 5 (very high).…”
Section: Methodsmentioning
confidence: 99%
“…Physical activity was assessed using both the short and long form of the International Physical Activity Questionnaire (IPAQ) at baseline. In accordance with the IPAQ scoring protocol [18], data from both forms were used to calculate categorical (low, moderate, high) physical activity scores by sex-specific total metabolic expenditure (MET-minutes/week) tertiles [19]. Participants categorized as moderately active met any of the following three criteria: (1) engaged in ≥3 days/week of vigorous-intensity activity of at least 20 min/day; or (2) ≥5 days of moderate-intensity activity or walking at least 30 min/day; or (3) ≥5 days of any combination of walking or moderate-or vigorous-intensity activities, achieving a minimum of 6 MET-minutes/week.…”
Section: Physical Activitymentioning
confidence: 99%